2006
DOI: 10.1007/s11104-005-3035-4
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR Relaxometry in Natural Humous Soil Samples: Insights in Microbial Effects on Relaxation Time Distributions

Abstract: 1 H NMR relaxometry is applied for the investigation of pore size distributions in geological substrates. The transfer to humous soil samples requires the knowledge of the interplay between soil organic matter, microorganisms and proton relaxation. The goal of this contribution is to give first insights in microbial effects in the 1 H NMR relaxation time distribution in the course of hydration of humous soil samples. We observed the development of the transverse relaxation time distribution of the water proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 37 publications
(55 reference statements)
5
38
0
Order By: Relevance
“…These findings were attributed to a redistribution of water during swelling. Todoruk et al [6] identified two processes with time constants of about 1 d for a fast process and up to 22 d for a slow process for different soils, which were comparable to the values reported by Schaumann et al [2,12] and Jaeger et al [13]. The calculated activation energies of these two processes ranged from 14 kJ mol -1 to 117 kJ mol -1 suggesting diffusion processes and chemical reactions, such as ester hydrolysis [6].…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…These findings were attributed to a redistribution of water during swelling. Todoruk et al [6] identified two processes with time constants of about 1 d for a fast process and up to 22 d for a slow process for different soils, which were comparable to the values reported by Schaumann et al [2,12] and Jaeger et al [13]. The calculated activation energies of these two processes ranged from 14 kJ mol -1 to 117 kJ mol -1 suggesting diffusion processes and chemical reactions, such as ester hydrolysis [6].…”
Section: Introductionsupporting
confidence: 73%
“…Additionally to the calculation of Q, 1 H NMR relaxometry [2,6,7,12,13] and DSC [7,14] were used to study the hydration of peat and mineral soil samples or to characterise different types of water in peats. DSC was used to study the melting and freezing behaviour of water and to calculate the amounts of non-freezable and freezable water in hydrogels [15,16] or peat soil samples [7,14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations